Two new species of freshwater crab of the genus neostrengeria pretzmann, 1965, from colombia (crustacea: decapoda: pseudothelphusidae), with an updated key of the species of the genus (2008)
We describe two new species of Neostrengeria Pretzmann, 1965, N. bataensis, from Santa María, Boyacá Department, and N. celioi, from Aguazul, Casanare Department, on the eastern slope of the Eastern Andes. With the addition of the new species, the number of species in the genus rises to 23. These new species are distinguished from their congeners primarily by the morphology of the first male gonopod, particularly by the shape of the lateral and accessory lobes, outline of apex, mesocaudal projection and mesial lobe. The genus Neostrengeria is endemic to Colombia and is distributed in both slopes and the high plain of the Eastern Cordillera, at elevations ranging from 470 to 3000 m. We present a key for the identification of the species based essencially on the morphology of the first male gonopod and pereopods